Planejamento em educação física escolar: perspectivas x realidade - Dezotti, Tálita Cristiane Dardes (Universidade Federal de São Carlos, 2020)
The act of planning for the teacher is necessary to organize what and how certain content will be developed. In the municipality of this study, there is no curriculum for the Physical Education curriculum component or proposals for the work of this active teacher. The National Common Curricular Base is the document that currently guides and suggests what can be studied in each school phase, offering a structure for each network to develop its own curriculum, however it is a recent document and is in the implementation phase. , therefore, at this moment, the debate on several themes becomes very pertinent, among them, teaching planning. The study aimed to investigate how Physical Education teachers from a public municipal network in the interior of the state of São Paulo, carry out their planning, dialoguing with their perspectives and needs in teaching practice. Professional training, from initial to continuing, the political pedagogical project and the documents that govern Brazilian education, are elements contemplated in this study and which are interrelated with planning in the exercise of teaching. The methodological trajectory of this qualitative research, of the participant research type, used the semi-structured interview as a data collection instrument, chosen for allowing explorations about the answers, in addition to having the descriptive memorial of the researcher teacher, who is also an active teacher in the studied network. The record of the data collections was through the transcriptions of the recordings of the interviews and later interpreted through the content analysis and triangulated with the researched bibliographic review. The expectation of the work, in addition to identifying the objectives, intrinsically wanted to favor reflection and a possible exchange of experiences, enabling a look at the planning itself in the face of a reality that, despite guaranteeing the component mentioned in the school, does not guarantee its systematization. Regarding the results, the surveyed professors said they carried out and carried out their plans despite pointing out, for the most part, that the lack of adequate space and materials was a major obstacle, and the lack of continuing education was also cited as a disincentive. Despite this, they have slightly different conceptions and directions in relation to the objectives of their planning, realizing that the network does not offer pedagogical support, characterizing the lack of organization for this curricular component.
Planning in school physical education: perspectives x reality
Keywords: Educação Física; Planejamento pedagógico; Exercício profissional; Physical Education; Planning; Pedagogical planning; Professional practice; CIENCIAS HUMANAS::EDUCACAO::PLANEJAMENTO E AVALIACAO EDUCACIONAL